Building a Central Repository for Research Ethics Consultation Data: A Proposal for a Standard Data Collection Tool. Issue 4 (10th March 2015) - Cho, Mildred K.; Taylor, Holly; McCormick, Jennifer B.; Anderson, Nick; Barnard, David; Boyle, Mary B.; Capron, Alexander M.; Dorfman, Elizabeth; Havard, Kathryn; Reider, Carson; Sadler, John; Schwartz, Peter; et al.
Abstract Clinical research ethics consultation services have been established across academic health centers over the past decade. This paper presents the results of collaboration within the CTSA consortium to develop a standard approach to the collection of research ethics consultation information to serve as a foundation for quality improvement, education, and research efforts. This approach includes categorizing and documenting descriptive information about the requestor, research project, the ethical question, the consult process, and describing the basic structure for a consult note. This paper also explores challenges in determining how to share some of this information between collaborating institutions related to concerns about confidentially, data quality, and informatics. While there is much still to be learned to improve the process of clinical research ethics consultation, these tools can advance these efforts, which, in turn, can facilitate the ethical conduct of research.